2003
DOI: 10.1590/s0103-64402003000300008
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CD8 and CD20 lymphocytes in chronic periapical inflammatory lesions

Abstract: The objective of this study was to investigate the distribution of CD8+ and CD20+ lymphocytes in chronic periapical inflammatory lesions. A total of 90 periapical inflammatory lesions (chronic abscesses, abscessed cysts, and inflammatory cysts) were evaluated. The biotin-streptavidin immunohistochemical technique was used to identify cytotoxic/suppressor T-lymphocytes (CD8) and B-lymphocytes (CD20). Age ranged from 10 to 67 years. Patients between 26 and 45 years old (54.4%), females (52.2%), and white patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(15 reference statements)
3
7
0
1
Order By: Relevance
“…The humoral immune response, mediated by B lymphocytes, is the main immune mechanism against extracellular microorganisms and their toxins, since antibodies bind to them to facilitate their removal. Cellular immunity, mediated by T lymphocytes, promotes the destruction of cells infected by intracellular microorganisms, as the antibodies are unable to attracting these antigens (Philippi et al , 2003). T and B lymphocytes are programmed to respond to specific antigens, and frequently, T lymphocytes consistently exceed B cell infiltration in periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The humoral immune response, mediated by B lymphocytes, is the main immune mechanism against extracellular microorganisms and their toxins, since antibodies bind to them to facilitate their removal. Cellular immunity, mediated by T lymphocytes, promotes the destruction of cells infected by intracellular microorganisms, as the antibodies are unable to attracting these antigens (Philippi et al , 2003). T and B lymphocytes are programmed to respond to specific antigens, and frequently, T lymphocytes consistently exceed B cell infiltration in periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in agreement with other authors (Liapatas et al , 2003; Philippi et al , 2003), we found that the number of T‐helper lymphocytes was similar or slightly increased compared to that of T‐suppressor/cytotoxic cells, both in the epithelium and in the fibrous capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the intensity of the inflammatory infiltrate showed a larger median number of CD8 + T lymphocytes in lesions with a grade III infiltrate (79.95) compared to those with a grade I/II infiltrate (62.0), but the difference was not statistically significant (P=0.725). According to Philippi et al, 12 the concentration and distribution of CD8 + T lymphocytes are directly associated with the concentration of antigens in periapical lesions. Muglali et al 32 emphasized the importance of proinflammatory cytokines such as IL-1 and TNF-α for the pathogenesis of periapical lesions, including the activation of osteoclasts, production and secretion of matrix metalloproteinases and stimulation of keratinocyte proliferation, as well as promotion of inflammatory cells recruitment.…”
Section: Cd8mentioning
confidence: 99%
“…These findings also suggest an important role of the adaptive immunity in the pathogenesis of chronic periapical lesions. 12,13,14,15 We emphasize that the integrity of the immune system is essential for the defense against infectious organisms and their toxic products. Immunodeficiency can compromise the number and activation of NK cells and CD8 + T lymphocytes, resulting in defects in the effector mechanisms of innate and adaptive immunity, thus leading to increased susceptibility for and difficulty in controlling infections.…”
mentioning
confidence: 99%
“…15 In case of increased caspase-3 activity, B cell pr oliferation was decreased. It was demonstrated by the results of in vivo study on caspase-3-deficient mice that caspase-3 regulated homeostasis in B cell.…”
Section: 10mentioning
confidence: 99%